1996
DOI: 10.1071/ar9960953
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile of adipose tissue and performance of feedlot steers supplemented with dehulled cottonseed and sunflower seed meal protected from ruminal metabolism

Abstract: The effect of feeding dehulled cottonseed protected from ruminal metabolism (PCS). Together with supplements of protected sunflower seed meal (PSM), on the performance and fatty acid profile of adipose tissue in feedlot steers was examined. Sixty-two Hereford cross steers, average weight 470 kg, were assigned to 4 groups and fed rations based on barley-corn silage for 150 days. The diets offered contained 10% untreated whole cottonseed +6% untreated sunflower seed meal (Group I), 10% PCS + 10% PSM (Group 11), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…There was no significant difference (P>0.05) between treatments 1 and 2 in FCR's but cattle on treatment 3 (20% MOC) showed significantly better feed conversion efficiency than those on the other two treatments. These results are in agreement with those reported by Gulati et al (1996) who indicated an improved FCR when dehulled cottonseed and sunflower meal were fed to feedlot steers at different levels. Table 4 shows the warm carcass masses and dressing percentages of cattle fed three levels of MOC.…”
Section: Resultssupporting
confidence: 95%
“…There was no significant difference (P>0.05) between treatments 1 and 2 in FCR's but cattle on treatment 3 (20% MOC) showed significantly better feed conversion efficiency than those on the other two treatments. These results are in agreement with those reported by Gulati et al (1996) who indicated an improved FCR when dehulled cottonseed and sunflower meal were fed to feedlot steers at different levels. Table 4 shows the warm carcass masses and dressing percentages of cattle fed three levels of MOC.…”
Section: Resultssupporting
confidence: 95%
“…The latter have been shown to alter bovine adipose tissue fatty acid composition markedly (19)(20)(21), as the caseinformaldehyde protection prevents ruminal hydrogenation of ingested fatty acids. Compared to cattle of similar genotype raised in the United States and fed corn-based diets for 100 d (13), the MUFA1 group was enriched with 18:1 (49 vs. 40%) and 16:1 (5 vs. 3%), and was notably lower in 18:0 (10 vs. 15%).…”
Section: Discussionmentioning
confidence: 97%
“…Where cyclopropenoic acids were detected in adipose tissues of rats, it was fed at subacute levels (14). Feeding formaldehyde-protected fatty acid supplements such as CSO has been reported to improve growth performance and to alter the fat composition of cattle quite dramatically (18). CSO is highly unsaturated, having more than 50% 18:2 (19), and high percentages of 18:2 (up to 10%) were found in adipose tissue of cattle fed protected CSO (18).…”
Section: Discussionmentioning
confidence: 98%
“…Feeding formaldehyde-protected fatty acid supplements such as CSO has been reported to improve growth performance and to alter the fat composition of cattle quite dramatically (18). CSO is highly unsaturated, having more than 50% 18:2 (19), and high percentages of 18:2 (up to 10%) were found in adipose tissue of cattle fed protected CSO (18). As significant amounts of dietary 18:2 were deposited in fat tissues, clearly some portion of these polyunsaturated fatty acids were protected from hydrogenation in the rumen.…”
Section: Discussionmentioning
confidence: 99%